2015
DOI: 10.1002/ijc.29676
|View full text |Cite
|
Sign up to set email alerts
|

ANOTCH1gene copy number gain is a prognostic indicator of worse survival and a predictive biomarker to a Notch1 targeting antibody in colorectal cancer

Abstract: Dysregulation of the Notch1 receptor has been shown to facilitate the development and progression of colorectal cancer (CRC) and has been identified as an independent predictor of disease progression and worse survival. Although mutations in the NOTCH1 receptor have not been described in CRC, we have previously discovered a NOTCH1 gene copy number gain in a portion of CRC tumor samples. Here, we demonstrated that a NOTCH1 gene copy number gain is significantly associated with worse survival and a high percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…One previous study from our laboratories on the Notch signalling pathway, preliminarily found that Notch1 acts as an oncogene in UCB . In various studies concerning other types of tumours, Notch signalling also shows oncogenic function . It has been widely acknowledged that Notch mediators include the Hes family, Hey family, nuclear factor‐κB, vascular growth factor receptor , and there are other Notch mediators yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…One previous study from our laboratories on the Notch signalling pathway, preliminarily found that Notch1 acts as an oncogene in UCB . In various studies concerning other types of tumours, Notch signalling also shows oncogenic function . It has been widely acknowledged that Notch mediators include the Hes family, Hey family, nuclear factor‐κB, vascular growth factor receptor , and there are other Notch mediators yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…(3)(4)(5)(6)(7)(8) Additionally, it has been shown that Notch signaling is strongly activated in primary human colorectal cancer (CRC) and has an important role in the initiation and progression of CRC through the regulation of apoptosis, proliferation, angiogenesis and cell migration. (9)(10)(11)(12)(13)(14) Recent reports have also indicated that JAG1 mediates the activation of Notch signaling in CRC and induces CRC progression. (15)(16)(17)(18)(19) Thus, the JAG1-Notch pathway has been regarded an attractive target for CRC therapy.Although high expression of JAG1 and the prognostic implications of Notch receptors in cancer cells have been described, (11)(12)(13)(14)(16)(17)(18)(19)(20) the prognostic significance of high JAG1 expression in CRC has not been determined.…”
mentioning
confidence: 99%
“…(9)(10)(11)(12)(13)(14) Recent reports have also indicated that JAG1 mediates the activation of Notch signaling in CRC and induces CRC progression. (15)(16)(17)(18)(19) Thus, the JAG1-Notch pathway has been regarded an attractive target for CRC therapy.Although high expression of JAG1 and the prognostic implications of Notch receptors in cancer cells have been described, (11)(12)(13)(14)(16)(17)(18)(19)(20) the prognostic significance of high JAG1 expression in CRC has not been determined. Therefore, we investigated the association of JAG1 protein expression with survival and recurrence in CRC by immunohistochemistry (IHC) using postoperative specimens and survey information on CRC prognosis collected in our research institute.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It also positively regulated the proliferation, colony formation, cell cycling, and tumorsphere formation of human colon cancers [106]. The elevated copy number gain of NOTCH1 together with its mRNA overexpression made it an independent predictor of prognosis in CRC [107, 108]. In colorectal carcinoma cells, NOTCH1-deppendent activation of cell cycle and proliferation were mediated by repression of cyclin-dependent kinase inhibitor p27.…”
Section: Introductionmentioning
confidence: 99%